AWARENESS ABOUT THE ORAL CANCER AMONG UNDERGRADUATE STUDENTS OF ALLIED HEALTH SCIENCES IN PESHAWAR. - UROOJ , A; UZMA, .; SAFDAR , A; FAISAL, .; NUMAN , M (Biological and Clinical Sciences Research Journal, 2024)
Oral cancer is a malignancy that affects the lips or oral cavity. Oral cancer causes about 20000 deaths worldwide. In Pakistan, it is the second most prevalent kind of cancer. The main obstacle to early diagnosis of oral cancer is the lack of information about oral cancer. Therefore, raising awareness among students is necessary and very helpful in controlling, early identification and prevention of oral cancer. Objective: To assess the level of awareness regarding oral cancer among undergraduate students. Methods. A descriptive cross-sectional study was carried out among undergraduate students of Allied Health Sciences Institutes in Peshawar. Data were collected from 312 undergraduate students through questionnaires. A convenient sampling technique was used for participant selection. Written informed consent was taken from all participants. Results: Out of 312 participants there were 124(39.7%) females and 188(60.3%) were males. About 65.7% were aware of oral cancer, and 71.2% were aware that oral cancer is due to alcohol drinking habits. 79.2% were aware that consumption of paan masala or guthka may cause oral cancer. 70.8% were aware that oral cancer is an infectious disease. Most of the students had poor knowledge regarding oral cancer as a disease of old age. Only 58.9% had information concerning the prevention of oral cancer. The majority of students were unaware of the treatment cost of oral cancer. More than half of the students (78.5%) were interested in information and education regarding oral cancer. Conclusion: The study concluded that students are decent or moderately aware. However, many lack basic knowledge regarding the initial signs and symptoms of oral cancer and its subsequent causes and effects, which could minimize the approach to overcoming the said problem.